2012
DOI: 10.1016/j.bandc.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of acquired color category effects

Abstract: a b s t r a c tCategory training can induce category effects, whereby color discrimination of stimuli spanning a newly learned category boundary is enhanced relative to equivalently spaced stimuli from within the newly learned category (e.g., categorical perception). However, the underlying mechanisms of these acquired category effects are not fully understood. In the current study, Event-Related Potentials (ERPs) were recorded during a visual oddball task where standard and deviant colored stimuli from the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 40 publications
4
53
2
Order By: Relevance
“…Electrophysiological studies have claimed that color categories modulate components of visually evoked event-related potentials that potentially arise from the visual cortex (10)(11)(12). However, it has been argued that inequalities in color metric or lack of clarity over the identity and origin of the event-related potential component complicate the interpretation of these findings (8). Using a very different approach, a behavioral-anatomical study found that the learning of novel color names was correlated with gray matter increases in V2/V3 (25).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Electrophysiological studies have claimed that color categories modulate components of visually evoked event-related potentials that potentially arise from the visual cortex (10)(11)(12). However, it has been argued that inequalities in color metric or lack of clarity over the identity and origin of the event-related potential component complicate the interpretation of these findings (8). Using a very different approach, a behavioral-anatomical study found that the learning of novel color names was correlated with gray matter increases in V2/V3 (25).…”
Section: Significancementioning
confidence: 99%
“…The origin and nature of such color categories has been extensively debated across the cognitive sciences (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Traditionally, debate has focused on whether color categories are biologically constrained (2,3), or whether they are arbitrary linguistic constructs that arise out of culture and communication (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been uncertainty about whether color category effects really do occur at a perceptual level, as the term "categorical perception" would suggest [11][12][13][14][15]. Psychophysical studies have disagreed whether categorical effects are present at detection threshold [13] or not [14].…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical studies have disagreed whether categorical effects are present at detection threshold [13] or not [14]. Distinguishing different-category colors may be easier than same-category colors because the categorical difference enhances attention [15]. Alternatively, a same-category disadvantage could arise because same-category colors have the same name despite being different colors, which leads to conflict at the stage of decision making [11].…”
Section: Introductionmentioning
confidence: 99%